Augmented Reality Technology in Learning Arabic Vocabulary from the Perception of University Students - Mus'ab Sahrim; Nor Fatini Aqilah Mohamad Soad; Lily Hanefarezan Asbulah (International Federation of Engineering Education Societies (IFEES), 2024)
Indexed by Scopus/ERA